2015
DOI: 10.1177/1748048515597873
|View full text |Cite
|
Sign up to set email alerts
|

Combining detached watchdog journalism with development ideals: An exploration of Fijian journalism culture

Abstract: Development journalism has been a key focus of discussion among journalism scholars for around half a decade, but most of the attention has been firmly on African and Asian countries. This article examines the situation on the little-researched island nation of Fiji, which has experienced considerable political instability since independence in 1970. Based on interviews with 77 of the country's small population of just over 100 journalists, we find that journalism in Fiji exhibits similarities to Western journ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 23 publications
3
22
1
1
Order By: Relevance
“…The results in the current study mirrored some of those in the previous Fiji study by Hanusch and Uppal (2015) carried out in 2008 and 2009. For example, in this study 90 percent of journalists ranked their role 'to monitor and scrutinise political leaders as 'extremely or very important', compared to 87 percent in the study carried out six years earlier.…”
Section: Perceptions Of Journalism Rolessupporting
confidence: 90%
See 3 more Smart Citations
“…The results in the current study mirrored some of those in the previous Fiji study by Hanusch and Uppal (2015) carried out in 2008 and 2009. For example, in this study 90 percent of journalists ranked their role 'to monitor and scrutinise political leaders as 'extremely or very important', compared to 87 percent in the study carried out six years earlier.…”
Section: Perceptions Of Journalism Rolessupporting
confidence: 90%
“…It is fair to anticipate some concern about the scientific rigour of the survey and the sample size, however 40 respondents to a survey in a media environment like Fiji's could be considered indicative of several factors. A previous study estimated journalists in Fiji at about 100 (Hanusch & Uppal, 2015). A list of more than 180 journalists, editors, photographers, and other news production workers was drawn up, with the estimated population size between 180 and 220.…”
Section: Scope and Limitations Of The Studymentioning
confidence: 99%
See 2 more Smart Citations
“…On election day, September 17, joining the 413 local media workers registered by MIDA and the Fijian Elections Office to cover Fiji's first national polls in eight years, were 37 foreign journalists (Naleba, 2014). Studies have shown that Fiji's journalistic cadre is relatively young (Hanusch & Uppal, 2015;Robie, 2004). Combined with the industry's high turnover rate and the immense brain drain of experienced editors and journalists after 2000 and 2006, this would have meant that in 2014 many journalists would have been covering their first general election, one in which they would also have voted for the first time.…”
Section: The Media and The Electionmentioning
confidence: 99%